2011
DOI: 10.1007/s10936-011-9186-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Family Size on Spanish Simple and Complex Words

Abstract: This study presents the results of three experiments in which the Family Size (FS) effect is explored. The first experiment is carried out with no prime on simple words. The second and third experiments are carried out with morphological priming on complex words. In the first experiment a facilitatory effect of FS is observed: high FS targets produced faster responses than low FS targets. However, an inhibitory effect of Stem-FS is observed in the second experiment: low Stem-FS targets produced faster response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Specifically, the higher the frequency of a suffix and the larger the family size of a suffix, the shorter the latencies. In accordance with our results, previous studies have also found facilitatory effects of suffix frequency (Baayen et al, 2007;Burani & Thornton, 2003; and suffix family size (Bertram, Baayen, & Schreuder, 2000;Lázaro & Sainz, 2012;. It is noteworthy that in our study in French, as in our parallel analyses in English , suffix frequency and suffix family size were highly associated.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, the higher the frequency of a suffix and the larger the family size of a suffix, the shorter the latencies. In accordance with our results, previous studies have also found facilitatory effects of suffix frequency (Baayen et al, 2007;Burani & Thornton, 2003; and suffix family size (Bertram, Baayen, & Schreuder, 2000;Lázaro & Sainz, 2012;. It is noteworthy that in our study in French, as in our parallel analyses in English , suffix frequency and suffix family size were highly associated.…”
Section: Discussionsupporting
confidence: 93%
“…This series is carried out in Spanish, an interesting language given its extremely shallow orthography (in contrast to English and French) and its highly productive derivational system. Previous evidence in Spanish has shown an important role for suffixes in word recognition (Duñabeitia, Perea & Carreiras, 2008;Lázaro & Sainz, 2012;, but this evidence was not obtained in the context of pseudoword priming. With the overall existing evidence, assumptions about the role of morphology within this experimental paradigm cannot be straightforward because i) totally divergent results have been obtained in previous studies; ii) the previous studies were carried out in languages other than Spanish -with different morphological and orthographic features; and iii) other studies did not control for the WEF, a potentially confounding variable.…”
Section: Controlmentioning
confidence: 74%
“…Our results fail to show such well-documented effects and we believe the most reasonable explanation is related to the methodologies themselves. When suffixes and non-morphemic endings are presented as primes (dad-> igualdad; Duñabeitia et al, 2008;Lázaro & Sainz, 2012;Lázaro, Illera, & Sainz, 2015a), when complex stimuli are anticipated by unmasked primes (Lázaro, Illera, & Sainz, 2015b), or when complex words are presented as primes sharing or not the same suffixes as targets (brevedad -> igualdad; Duñabeitia et al, 2008), then the role of suffixes in morphological processing becomes evident. However, when complex words and complex and simple pseudowords are presented in a masked priming lexical decision, the role of suffixes and morphological decomposition seems to have no relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Evidently, the role of a grammatical morpheme can differ from that of a lexical morpheme when processing complex words, thus justifying the distinction between composition and derivation; (4) besides the above, the features of each particular language determine other areas of interest for the psycholinguistic study of reading. For example, Lázaro and Sainz () or Sainz, Sainz and Lázaro () underlined that while in Dutch and English, stem family size can be in the hundreds – probably due, to a certain extent, to their compositional richness – in the corpus of Spanish words in their study, no word had a family size above 15. Thus, each language has its own individual characteristics that diverge from those of other languages, despite the fact the languages might be related.…”
Section: Introductionmentioning
confidence: 98%